1984
DOI: 10.1007/bf00262219
|View full text |Cite
|
Sign up to set email alerts
|

Augmented gastrin responses in diabetic patients with vagal neuropathy

Abstract: Summary.We evaluated serum gastrin responses to a test meal in normal subjects and diabetic patients with or without vagal neuropathy. Vagal neuropathy was defined as a heart rate variation during deep breathing of < 9 beats/min. Forty-three percent (54 out of 124) of the diabetic patients had abnormal heart rate variation, compared with 5% (3 out of 53) of the normal subjects. Serum gastrin responses to a test meal were examined in 17 normal subjects, 20 out of 70 diabetic patients without vagal neuropathy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[13][14][15] Thus, when the branches of the vagus that innervate the heart are affected, the more distal branches of the vagus, such as the gastric nerve, are affected. [16][17][18][19][20] Cardio-vagal neuropathy was based on heart rate (HR) variability in response to deep breathing. Heart rate was recorded using a standard ECG monitor.…”
Section: Study Populationmentioning
confidence: 99%
“…[13][14][15] Thus, when the branches of the vagus that innervate the heart are affected, the more distal branches of the vagus, such as the gastric nerve, are affected. [16][17][18][19][20] Cardio-vagal neuropathy was based on heart rate (HR) variability in response to deep breathing. Heart rate was recorded using a standard ECG monitor.…”
Section: Study Populationmentioning
confidence: 99%
“…tn the present study we have evaluated the integrity of the autonomic nervous system in gastroparesis in patients with type II diabetes using the aforementioned noninvasive methods, with a particular emphasis on gastric emptying rate and plasma concentrations of gastrin after a standard solid and liquid labeled with radionuclide meal to see whether the response of this substance may serve as a simple test to distinguish between patients with diabetes with AN and those without AN [10,11] …”
mentioning
confidence: 99%
“…The elevated gastrin concentrations cannot be explained by atrophic gastritis in this study since only one subject had this condition. However, the elevation could be a result of a disturbed feedback mechanism due to neuropathy in the stomach [6], vagal neuropathy [16,17], an increased quantity of gastrin cells in the stomach [43], reduced number of somatostatin cells [44], or hyperglycaemia [45]. …”
Section: Resultsmentioning
confidence: 99%
“…Cholecystokinin (CCK) and gastrin are released from endocrine cells in the upper GI tract in response to food, and they influence relaxation of the lower oesophageal sphincter (LOS), gastric acid secretion, gastric emptying, growth of gastric mucosa, contraction of the gallbladder, pancreatic growth, enzyme secretion, and intestinal motility [14,15]. Earlier studies have reported increased CCK and gastrin concentrations in plasma from diabetics with autonomic neuropathy [16-20], whereas patients without neuropathy showed normal concentrations, irrespective of GI function [17,19-21]. Recently, receptors for vasopressin, a peptide hormone homologous to oxytocin, have also been found in the GI tract [22], and vasopressin has been shown to affect the electrical rhythm in the human stomach [23,24].…”
Section: Introductionmentioning
confidence: 99%